Identification and characterization of the key enzyme in the biosynthesis of the neurotoxin beta-ODAP in grass pea - Goldsmith, Moshe; Barad, Shiri; Knafo, Maor; Savidor, Alon; Ben-Dor, Shifra; Brandis, Alexander; Mehlman, Tevie; Peleg, Yoav; Albeck, Shira; Dym, Orly; Ben-Zeev, Efrat; Barbole, Ranjit S.; et al. (Journal of Biological Chemistry, 2022)
Grass pea (Lathyrus sativus L.) is a grain legume commonly grown in Asia and Africa for food and forage. It is a highly nutritious and robust crop, capable of surviving both droughts and floods. However, it produces a neurotoxic compound, beta-N- oxalyl-L-alpha,beta-diaminopropionic acid (beta-ODAP), which can cause a severe neurological disorder when consumed as a primary diet component. While the catalytic activity associated with beta-ODAP formation was demonstrated more than 50 years ago, the enzyme responsible for this activity has not been identified. Here, we report on the identity, activity, 3D structure, and phylogenesis of this enzyme-beta-ODAP synthase (BOS). We show that BOS belongs to the benzylalcohol O-acetyltransfer-ase, anthocyanin O-hydroxycinnamoyltransferase, anthranilate N-hydroxycinnamoyl/benzoyltransferase, deacetylvindoline 4-O-acetyltransferase superfamily of acyltransferases and is structurally similar to hydroxycinnamoyl transferase. Using molecular docking, we propose a mechanism for its catalytic activity, and using heterologous expression in tobacco leaves (Nicotiana benthamiana), we demonstrate that expression of BOS in the presence of its substrates is sufficient for beta-ODAP production in vivo. The identification of BOS may pave the way toward engineering beta-ODAP-free grass pea cultivars, which are safe for human and animal consumption.